The falling between us - Parsons, Ash (New York, NY : Philomel Books, 2018)
At fifteen, Joshua Blackbird becomes an international singing star but, as his hometown girlfriend relates, after more than a year, the pressures and dangers of fame take a toll and "Shu" disappears.
Keywords: Fame -- Juvenile fiction; Missing persons -- Juvenile fiction; Singers -- Juvenile fiction; Popular music -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Fame -- Fiction; Missing persons -- Fiction; Singers -- Fiction; Popular music -- Fiction; Dating (Social customs) -- Fiction; YOUNG ADULT FICTION -- Mysteries & Detective Stories; YOUNG ADULT FICTION -- Performing Arts -- Music; YOUNG ADULT FICTION -- Thrillers & Suspense; Missing persons -- Young adult fiction; Popular music -- Young adult fiction; Dating (Social customs) -- Young adult fiction; Fame -- Young adult fiction; Singers -- Young adult fiction; Fiction; Juvenile works; Novels